Student attitudes toward e-learning- A study at the Institute of Science and Techniques of Physical and Sports Activities at University of Souk Ahras - khlifi salim (sports creativity, 2025)
The study aims to identify the attitudes of students of the Institute of Science and Techniques of Physical and Sports Activities at University of Souk Ahras towards e-learning, for this purpose the researcher relied on the descriptive analytical method using a questionnaire distributed to a sample of 50 students where the results were statisticallyprocessed using the SPSS program. The study reached that students have positive attitudes toward e-learning, and there are no differences in these attitudes due to the variable age, and there are differences among them in sex variables, school level, specialization, economic level of parents, computer possession and internet connection.